Molecular Epidemiology of Rhinovirus Detections in Young Children. (13th January 2016) - Howard, Leigh M.; Johnson, Monika; Gil, Ana I.; Griffin, Marie R.; Edwards, Kathryn M.; Lanata, Claudio F.; Williams, John V.; Grijalva, Carlos G.; ,; Griffin, Marie R.; Williams, John V.; Howard, Leigh M.; et al.
Abstract: Background.  Human rhinoviruses (HRVs) are frequently detected in children with acute respiratory illnesses (ARIs) but also in asymptomatic children. We compared features of ARI with HRV species (A, B, C) and determined genotypes associated with repeated HRV detections within individuals. Methods.  We used clinical data and respiratory samples obtained from children <3 years old during weekly active household-based surveillance. A random subset of samples in which HRV was detected from individuals during both ARI and an asymptomatic period within 120 days of the ARI were genotyped. Features of ARI were compared among HRV species. Concordance of genotype among repeated HRV detections within individuals was assessed. Results.  Among 207 ARI samples sequenced, HRV-A, HRV-B, and HRV-C were detected in 104 (50%), 20 (10%), and 83 (40%), respectively. Presence of fever, decreased appetite, and malaise were significantly higher in children with HRV-B. When codetections with other viruses were excluded (n = 155), these trends persisted, but some did not reach statistical significance. When 58 paired sequential HRV detections during asymptomatic and ARI episodes were sequenced, only 9 (16%) were identical genotypes of HRV. Conclusions.  Clinical features may differ among HRV species. Repeated HRV detections in young children frequently represented acquisition of new HRV strains.